2003
DOI: 10.1093/qjmed/hcg031
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in adults due to glucose non-fermentative Gram-negative bacilli other than P. aeruginosa

Abstract: NF bacteraemia mainly affects patients with malignant haematological disease, with and without transplantation, and patients in the ICU. The most common known source is a central venous catheter, though many sources are unknown. Mortality is relatively low, and depends on the severity of the underlying disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
2
29
0
2
Order By: Relevance
“…The electrokaryotypes of four clinical isolates of C. meningosepticum were similar to those of faucet isolates. Measures directed at making the water supply safe may prevent infection by C. meningosepticum and other waterborne pathogens.Nosocomial infections caused by nonfermentative gram-negative bacilli (NFGNB) are increasing in intensive care units (ICUs) (19,20,27). Pseudomonas aeruginosa, Acinetobacter baumannii, and Stenotrophomonas maltophilia account for most endemic infections.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The electrokaryotypes of four clinical isolates of C. meningosepticum were similar to those of faucet isolates. Measures directed at making the water supply safe may prevent infection by C. meningosepticum and other waterborne pathogens.Nosocomial infections caused by nonfermentative gram-negative bacilli (NFGNB) are increasing in intensive care units (ICUs) (19,20,27). Pseudomonas aeruginosa, Acinetobacter baumannii, and Stenotrophomonas maltophilia account for most endemic infections.…”
mentioning
confidence: 99%
“…and Sphingomonas spp. are particularly troublesome (19,20,27).Hospital water has been shown to be a significant source of health care-associated infections caused P. aeruginosa in ICUs (4,15,17,18,25,26). Trautmann et al (24) reported that P. aeruginosa could be frequently recovered from tap water outlets in ICUs and that the same genotypes were recovered from colonized or infected patients (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient had several predisposing conditions for invasive soft tissue and bloodstream infections. Chronic hemodialysis and corticosteroid use have previously been shown to be risk factors for Gram-negative rod bacteremia (18,20). Whether prior splenectomy in our patient contributed to infection with S. marcescens is not entirely clear.…”
mentioning
confidence: 77%
“…First, it focused mainly on B. cepacia and S. maltophilia infections in trauma patients, a population largely devoid of other medical comorbidities, whereas most reported studies have focused on patients with cystic fibrosis (Spicuzza et al, 2009;Waters et al, 2013;CorreaRuiz et al, 2013). Second, our study attempted to distinguish those with true infections based on CDC definition and not just mere colonisation, whereas other studies failed to differentiate true infections from colonisation (Vidal et al, 2003). Third, monthly and yearly distributions of these two bacteria along with antibiotic resistance patterns were observed, compared and analysed.…”
Section: Discussionmentioning
confidence: 99%